A Statistical Analysis of the Performance Variability of Read/Write Operations on Parallel File Systems - Inacio, Eduardo C.; Barbetta, Pedro A.; Dantas, Mario A.R. (Procedia computer science, 2017)
This paper reports a statistical analysis about the performance variability of read and write operations on parallel file systems. To properly account for the inherent system variability and to obtain statistically significant results, formal experimental design and analysis methods were employed in this study. This research reveals that in the evaluated conditions six effects dominate I/O time, responding for 99.32% of the performance variability. Further, some factors traditionally explored in I/O optimization proposals presented no statistical evidence of significant effects in this study. Moreover, high-level effects were identified by the interpretation of the set of statistically significant factors, providing a case for further research in the subject.